Influência do alambique guilhotina em componentes voláteis da cachaça - Lorena de Oliveira Simão Marinho (2017)
Influence of Guilhotina alembic on volatile compounds of cachaça. The objective of this study was to evaluate the efficiency of guilhotina alembic on the physicochemical quality of cachaça. The performance of the equipment was investigated by itself and with two types of fillers (stainless steel and pall ring tubes) in the ascending part of the equipment (column), and also the association of the pall ring filling with addition of activated charcoal in the pan. Guillotine alembic was effective in reducing (ANOVA, 5%) acetaldehyde, ethyl acetate and ethyl carbamate (17.53%, 26.93%, and 5.6%, respectively). There was no variation on other parameters; however, there was an increase in methyl alcohol and acrolein. The use of both types of fillers reduced the contents of acetaldehyde, ethyl acetate (higher reductions were obtained with pall ring), and n-butyl alcohol. There was an increase in methyl alcohol, acrolein and ethyl carbamate contents (higher contents of ethyl carbamate using pall ring). The association of pall ring and activated charcoal reduced volatile acidity and ethyl carbamate compared to the absence of activated charcoal. However, compared to the original sample, there was reduction of acetaldehyde and ethyl acetate and increase of methyl alcohol and ethyl carbamate. The association with activated charcoal did not improve the reduction of the acetaldehyde and ethyl acetate contents; however, it was able to maintain the initial acrolein levels. Guilhotina alembic alone and with the introduction of variables (stainless steel tubes, pall ring and activated charcoal) were efficient in reducing acetaldehyde and ethyl acetate, and could be used to improve the sensory and toxicological quality of cachaça. The choice of the variable to be used in will depend on the initial characteristics of the cachaça to be treated